2019
DOI: 10.5688/ajpe7494
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pharmacy Student Consultations with Standardized Patients on Opioid Medication Use and Opioid-Specific Risks

Abstract: Objective. To assess third-year pharmacy students' entry-level verbal and nonverbal communication skills when addressing sensitive topics during opioid consultations with standardized patients. Methods. Seventy-one students were video-taped while consulting with standardized patients who were receiving a one-month supply of oxycodone for lower back pain. Consults were coded quantitatively for the topics students discussed with the patient, terms used, eye contact, and filler words. Results. The majority of pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…The study results herein are essential to pharmacy educators because student pharmacists must be competent in their abilities to counsel a patient about opioids, understand the mechanisms of addiction, and screen for opioid overuse, as these actions ultimately lead to harm reduction. Thakur et al assessed third-year student-pharmacists’ verbal and nonverbal communication skills during a simulated opioid counseling and found that many students lacked confidence in educating patients about opioid-specific risks such as dependence, addiction, or overdose [ 30 ]. This study also reinforced the need for additional education and resources on how to best communicate with patients about this sensitive topic [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study results herein are essential to pharmacy educators because student pharmacists must be competent in their abilities to counsel a patient about opioids, understand the mechanisms of addiction, and screen for opioid overuse, as these actions ultimately lead to harm reduction. Thakur et al assessed third-year student-pharmacists’ verbal and nonverbal communication skills during a simulated opioid counseling and found that many students lacked confidence in educating patients about opioid-specific risks such as dependence, addiction, or overdose [ 30 ]. This study also reinforced the need for additional education and resources on how to best communicate with patients about this sensitive topic [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thakur et al assessed third-year student-pharmacists’ verbal and nonverbal communication skills during a simulated opioid counseling and found that many students lacked confidence in educating patients about opioid-specific risks such as dependence, addiction, or overdose [ 30 ]. This study also reinforced the need for additional education and resources on how to best communicate with patients about this sensitive topic [ 30 ]. Pharmacy educators should focus their future efforts on harm reduction strategies that include counseling, how to address patients at risk of OUD, and how to screen patients who are at risk of OUD.…”
Section: Discussionmentioning
confidence: 99%
“…This need has also been identified at colleges of pharmacy across the United States and has recently sparked a wide range of educational approaches to this end, some of which have been already reported in the literature. [39][40][41]…”
Section: Reducing Stigma Through Pharmacist-provided Care To Normalize Treatmentmentioning
confidence: 99%
“…5 These students further reported the need for additional education and resources on communicating with patients about this sensitive topic. 5 Other studies have also reported on this gap in knowledge. [6][7][8][9] It is important to both meet the need for greater clinical knowledge and confidence in communicating with and treating OUD patients, and also understand students' own attitudes and beliefs towards patients of this vulnerable population.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study that assessed third-year student pharmacists’ verbal and nonverbal communication skills during a simulated opioid counseling session found that many students lacked confidence in educating patients about opioid-specific risks, such as dependence, addiction, or overdose. 5 These students further reported the need for additional education and resources on communicating with patients about this sensitive topic. 5 Other studies have also reported on this gap in knowledge.…”
Section: Introductionmentioning
confidence: 99%